THE EFFECT OF PRODUCT QUALITY AND PRODUCT DESIGN ON PURCHASING DECISIONS FOR ERSPO JERSEYS FOR THE INDONESIAN SOCCER NATIONAL TEAM WITH FANATICISM AS AN INTERVENING VARIABLE - Matondang, Muhammad Haekal; Anggraini, Tuti; Qarni, Waizul (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This study aims to see the effect of Product Quality and Product Design on Purchasing Decisions for Erspo jersey products for the Indonesian national football team with Fanaticism as mediation. This research uses a quantitative approach with data collection techniques using questionnaires distributed to 100 respondents who buy the jersey, this research was analyzed using Smart PLS 4.0. The results of this study indicate that Product Quality has no effect on Purchasing Decisions, Product Design has no effect on Purchasing Decisions, Fanaticism has an effect on Purchasing Decisions, Fanaticism cannot mediate the impact of Product Quality on Purchasing Decisions, Fanaticism cannot mediate the impact of Product Design on Purchasing Decisions. Which means that consumers do not care about the Product Quality and Product Design, consumers only follow their Fanaticism in supporting the National Team to buy Erspo Jersey products for the Indonesian National Soccer Team.